(untitled) (Research, Society and Development, 2023)
Introduction: Medication errors are currently a worldwide public health problem, the most serious being prescription errors. Errors arising from medical prescriptions can cause serious damage to the health of patients; therefore, it is imperative that they be identified and prevented. Objective: To analyze the main prescription errors in the Brazilian hospital environment. Methodology: The study is a systematic review, Results: 15 reports were selected for the development of this systematic review. Within these studies, the main prescription errors found were: illegibility; presence of abbreviations; lack of pharmaceutical form, route of administration, dose intervals and duration of treatment; dosage errors; drug interactions; prescriber identification failures; omission of patient data; ambiguous and confusing prescriptions. Some of the clinical impacts caused to patients due to prescribing errors can be: patient injuries that can be permanent or fatal; therapeutic ineffectiveness; adverse reactions and unnecessary drug interactions; possible nosocomial infections due to longer hospital stays and increased morbidity and mortality rates. Conclusion: There was a high prevalence of prescription errors in the hospital environment, both in relation to information regarding the patient, as well as information about the prescriber and medications. These errors become a high risk for patient safety, as they are vulnerable to possible adverse reactions, therapeutic ineffectiveness, which may lead to an increase in hospitalization time, and consequently, leaving the patient more prone to new infections, aggravating their condition. clinical.